Study of cyclic and steady particle motion in a realistic human airway model using phase-Doppler anemometry - Jedelský, Jan; Lízal, František; Jícha, Miroslav (EDP Sciences, 2010)
Transport and deposition of particles in human airways has been of research interest for many years. Various experimental methods such as constant temperature anemometry, particle image velocimetry and laser-Doppler based techniques were employed for study of aerosol transport in the past. We use Phase-Doppler Particle Analyser (P/DPA) for time resolved size and velocity measurement of liquid aerosol particles in a size range 1 to 8 um. The di-2-ethylhexyl sabacate (DEHS) particles were produced by condensation monodisperse aerosol generator. A thin-wall transparent model of human airways with non-symmetric bifurcations and non-planar geometry containing parts from throat to 3rd-4th generation of bronchi was fabricated for the study. Several cyclic (sinusoidal) breathing regimes were simulated using pneumatic breathing mechanism. Analogous steady-flow regimes were also investigated and used for comparison. An analysis of the particle velocity data was performed with aim to gain deeper understanding of the transport phenomena in the realistic bifurcating airway system. Flows of particles of different sizes in range 1-10 um was found to slightly differ for extremely high Stokes numbers. Differences in steady and cyclic turbulence intensities were documented in the paper. Systematically higher turbulence intensity was found for cyclic flows and mainly in the expiration breathing phase. Negligible differences were found for behaviour of different particle size classes in the inspected range 1 to 8 um. Possibility of velocity spectra estimation of air flow using the P/DPA data is discussed.

Transport and deposition of particles in human airways has been of research interest for many years. Various experimental methods such as constant temperature anemometry, particle image velocimetry and laser-Doppler based techniques were employed for study of aerosol transport in the past. We use Phase-Doppler Particle Analyser (P/DPA) for time resolved size and velocity measurement of liquid aerosol particles in a size range 1 to 8 um. The di-2-ethylhexyl sabacate (DEHS) particles were produced by condensation monodisperse aerosol generator. A thin-wall transparent model of human airways with non-symmetric bifurcations and non-planar geometry containing parts from throat to 3rd-4th generation of bronchi was fabricated for the study. Several cyclic (sinusoidal) breathing regimes were simulated using pneumatic breathing mechanism. Analogous steady-flow regimes were also investigated and used for comparison. An analysis of the particle velocity data was performed with aim to gain deeper understanding of the transport phenomena in the realistic bifurcating airway system. Flows of particles of different sizes in range 1-10 um was found to slightly differ for extremely high Stokes numbers. Differences in steady and cyclic turbulence intensities were documented in the paper. Systematically higher turbulence intensity was found for cyclic flows and mainly in the expiration breathing phase. Negligible differences were found for behaviour of different particle size classes in the inspected range 1 to 8 um. Possibility of velocity spectra estimation of air flow using the P/DPA data is discussed.
Study of cyclic and steady particle motion in a realistic human airway model using phase-Doppler anemometry
Keywords: cyclic and steady flow; particle motion; realistic human airway model; phase-doppler anemometry; cyclic and steady flow; particle motion; realistic human airway model; phase-doppler anemometry